2002
DOI: 10.1038/sj.bjc.6600157
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen induction of angiogenic factor expression in endometrium

Abstract: Tamoxifen is the current therapy of choice for patients with oestrogen receptor positive breast cancer, and it is currently under evaluation as a prophylactic for women at high risk of developing the disease. However, tamoxifen is also known to induce proliferative changes in the endometrium increasing the risk of developing endometrial hyperplasia, polyps and carcinoma. Angiogenesis is an intimate part of this process. For this reason, we have examined the expression of several well characterized angiogenic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…These observations suggest that estrogen indeed stimulates angiogenesis and thus tumor stromal growth, but that tamoxifen does not block those functions of the ER necessary for bone marrow cell recruitment and angiogenesis. Consistent with this notion, previous reports have indicated that tamoxifen does not inhibit the proangiogenic effects of estrogen in the uterus (49,50).…”
Section: Discussionsupporting
confidence: 74%
“…These observations suggest that estrogen indeed stimulates angiogenesis and thus tumor stromal growth, but that tamoxifen does not block those functions of the ER necessary for bone marrow cell recruitment and angiogenesis. Consistent with this notion, previous reports have indicated that tamoxifen does not inhibit the proangiogenic effects of estrogen in the uterus (49,50).…”
Section: Discussionsupporting
confidence: 74%
“…We were the ®rst to show that ADM is an angiogenic factor (Zhao et al, 1998). Furthermore we demonstrated that ADM expression in uterine leiomyomas (benign smooth muscle tumours) correlated with vascular density (Hague et al, 2000). In addition, we reported the presence of ADM in human endometrium where it was upregulated by the nonsteroidal antiestrogen tamoxifen (TAM) (Zhao et al, 1998).…”
Section: Introductionmentioning
confidence: 80%
“…Moreover, treatment with rPEDF restored the angiogenic balance by resisting tamoxifen-induced uterine VEGF elevation, as seen by the decrease of both uterine weight and CD34-marked blood vessels. Former evidence characterizing the changes in uterine vasculature after tamoxifen treatment in postmenopausal patients was not persistent, possibly due to limited sample size and increased heterogeneity (28,29).…”
Section: Discussionmentioning
confidence: 99%